ANALISIS PENGARUH PRIOR CHEATING BEHAVIOR, PRIOR WHISTLEBLOWING, DAN IPK TERHADAP WHISTLEBLOWING INTENTION (Studi Kasus Pada Mahasiswa S1 Akuntansi Universitas Brawijaya) - Hartono, Riska (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Students’ performance at the university may influence their behavior at the workplace. This research presents the test results regarding the effect of prior cheating behavior, prior whistleblowing, and Grade Point Average (GPA) on whistleblowing intention. The data are collected by means of questionnaires distributed to the undergraduate students majoring in Accounting at the University of Brawijaya batch 2016/2017. The data analysis shows that prior cheating behavior does not influence whistleblowing intention; whereas, prior whistleblowing and Grade Point Average (GPA) have a negative correlation to whistleblowing intention in the future. This study also reveals that the average of 112 students has recognized the academic dishonesty conducted by their peers but they prefer to act neutrally and do nothing. The result of the study can be used as a basis of evaluation by the Faculty of Economics and Business in the University of Brawijaya, particularly the Accounting department, in developing the reporting system of students’ academic dishonesty.Keywords: Academic dishonesty; GPA; Whistleblowing; College students